Identification of the R1 Oncogene and Its Protein Product from the Rhadinovirus of Rhesus Monkeys - Damania, Blossom (American Society for Microbiology, 1999)
Rhesus monkey rhadinovirus (RRV) is a gamma-2 herpesvirus that is most closely related to the human Kaposi’s sarcoma-associated herpesvirus (KSHV). We have identified a distinct open reading frame at the left end of RRV and designated it R1. The position of the R1 gene is equivalent to that of the saimiri transforming protein (STP) of herpesvirus saimiri (HVS) and of K1 of KSHV, other members of the gamma-2 or rhadinovirus subgroup of herpesviruses. The R1 sequence revealed an open reading frame encoding a product of 423 amino acids that was predicted to contain an extracellular domain, a transmembrane domain, and a C-terminal cytoplasmic tail reflective of a type I membrane-bound protein. The predicted structural motifs of R1, including the presence of immunoreceptor tyrosine-based activation motifs, resembled those in K1 of KSHV but were distinct from those of STP. R1 sequences from four independent isolates from three different macaque species revealed 0.95 to 7.3% divergence over the 423 amino acids. Variation was located predominantly within the predicted extracellular domain. The R1 protein migrated at 70 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and was extensively glycosylated. Tagged R1 protein was localized to the cytoplasmic and plasma membranes of transfected cells. Expression of the R1 gene in Rat-1 fibroblasts induced morphologic changes and focus formation, and injection of R1-expressing cells into nude mice induced the formation of multifocal tumors. A recombinant herpesvirus in which the STP oncogene of HVS was replaced by R1 immortalized T lymphocytes to interleukin-2-independent growth. These results indicate that R1 is an oncogene of RRV.